Modeling of the Deposition of Low-Density Lipoprotein Particles inside an Ideal Geometry of the Heart Coronary Arteries - Nima Sinafar; Ataallah Soltani Goharrizi; Bahador Abolpour (International Journal of Heart Research, 2022)
In this study, flow hemodynamic parameters and settling of LDL particles in healthy ideal and ideal with stenosis coronary artery have been studied using the Open FOAM software. Not only the effect of movement of the vessel on particles depositions have been studied, but also both non-Newtonian and Newtonian behaviors of blood have been investigated. The particle's motion and deposition have been simulated. It has resulted that only in small vessels, non-Newtonian behavior of blood can be seen and in bigger vessels, there is no remarkable difference between two Newtonian and non-Newtonian models. Vessel movement has no important effects on entered shear stress on its wall, but the alteration in flow lines causes a 70% increment in particles depositions on a vessel with stenosis. This shear stress has no considerable changes with inlet velocity alteration, but it has intensive dependence on geometry in the vessel with stenosis (13 times more oscillation in stenosis location than a healthy vessel).
Keywords: Coronary arteries